Transcripts of speeches presented at the International Monetary System in Transition : a symposium sponsored by the Federal Reserve Bank of Chicago, March 16-17, 1972 - The Federal Reserve Bank of Chicago (Chicago: The Federal Reserve Bank of Chicago, 1972)
This book contains the proceeding of a conference sponsored by the Federal Reserve Bank of Chicago. Papers presented centered on international monetary systems; balance of payments and foreign exchange market.
Includes bibliographical footnotes
usc 15/08/18
Loans
Keywords: International finance